The Bridging Role of Expatriates and Inpatriates in Knowledge Transfer in Multinational Corporations - Harzing, Anne‐Wil; Pudelko, Markus; Sebastian Reiche, B. (Human Resource Management, 2016)
Drawing on the knowledge‐based view of the firm, this article provides the first empirical study that explicitly investigates the relationship between different categories of international assignees and knowledge transfer in multinational corporations (MNCs). Specifically, we examine (1) the extent to which expatriate presence in different functional areas is related to knowledge transfer from and to headquarters in these functions and (2) the extent to which different categories of international assignees (expatriates vs. inpatriates) contribute to knowledge transfer from and to headquarters. We base our investigation on a large‐scale survey, encompassing data from more than 800 subsidiaries of MNCs in 13 countries. By disaggregating the role of knowledge transfer across management functions, directions of knowledge transfer, and type of international assignees, we find that (1) expatriate presence generally increases function‐specific knowledge transfer from and, to a lesser extent, to headquarters; and that (2) the relevance of expatriates and former inpatriates varies for knowledge flows between headquarters and subsidiaries. Additionally, we discuss implications for research and practice, in particular regarding different management functions and different forms of international assignments, and provide suggestions for future research. © 2015 Wiley Periodicals, Inc.